Holistic Digital Service Transformation of Motor Vehicle Tax as a Strategy to Enhance Compliance and Regional Original Revenue Realization: A Case Study : JEL Classification: H21, H26, H71, O33, R58 - Andi Arif; Gita Susanti; Muhammad Rusdi (Journal La Bisecoman, 2026)
The implementation of digital Motor Vehicle Tax (PKB) services in South Sulawesi faces significant challenges in low adoption rates despite the availability of technological infrastructure. This phenomenon indicates systemic barriers in the diffusion of innovation, including institutional resistance within the bureaucracy and socio-geographic as well as digital literacy obstacles among the public. This study aims to analyze adoption dynamics and identify critical barriers in the diffusion of digital PKB service innovation to formulate a holistic implementation strategy.This research employs a qualitative approach with an explorative case study method. Data were gathered through operational document analysis, in-depth interviews with key stakeholders (Bapenda, Ditlantas Polri, Jasa Raharja), and Focus Group Discussions (FGD) with diverse taxpayer groups. Findings show that relative advantage is the strongest predictor of adoption, where digital services can reduce the rigidity of 17 types of manual operational procedures that are rigid and labor-intensive. However, diffusion is hindered by organizational inertia, a lack of digital transformational leadership, and gaps in internet understanding among the heterogeneous society. The success of digital PKB transformation depends not only on technical sophistication but also on the organization's ability to build a collective digital culture and align innovation with the socio-psychological realities of taxpayers.